Development-aligned mangrove conservation strategy for enhanced blue economy: A successful model from Gujarat, India. (5th September 2022) - Shah, Hardik; Ramesh, R
Abstract: Mangrove protection and restoration have been prioritised in India, and as a result of concerted interventions by key maritime states, mangrove cover has increased significantly in the last few decades. Mangrove restoration efforts have received considerable attention in the States of Gujarat, Tamil Nadu, Odisha, and Andhra Pradesh for their role in the mitigation of storms and cyclones. The 'community-based restoration' strategy, in particular, is credited with expansion of mangrove regions across India. This study highlights the mechanism of successful mangrove restoration and conservation through various efforts of the government, private sector, and the coastal community in the state of Gujarat, India. Despite rapid coastal development, mangrove cover has also steadily increased in the last few decades in the State, clearly indicating a balanced approach towards enhancing blue economy. This is credited to the vision of the Government of Gujarat, India for putting in place appropriate policies and their effective implementation. Restoration of degraded mangrove and afforestation of new mangroves were made successful by applying scientific transplantation of saplings, utilization of local resources, involvement of public and private sectors and efficient monitoring activities. The Government of Gujarat has developed a comprehensive approach to integrate diverse sectors to effectively conserve mangroves and adopting a community-based restoration model. Such efforts at the regional level are the first-ever large-scale restoration and afforestation measures in India. Graphical abstract: Coupling mangrove conservation and coastal development for enhanced blue economy in India. Image 1 Highlights: Mangrove conservation and sustainable development in Gujarat emphasizes the "new blue" initiatives. Increase in mangrove cover attributed to the effective implementation of appropriate policies. Successful mangrove restoration model has multi-stakeholder participation. Mangrove conservation by Gujarat focused on enhanced ecosystem services.